Adverse events of bevacizumab for triple negative breast cancer and HER-2 negative metastatic breast cancer: A meta-analysis - Xun, Xueqiong; Ai, Jun; Feng, Fuhui; Hong, Pan; Rai, Saroj; Liu, Ruikang; Zhang, Baowen; Zhou, Yeming; Hu, Huiyong (Frontiers in Pharmacology, 2023)
Background: Triple-negative breast cancer (TNBC) and HER-2 negative metastatic breast cancer (HER-2 negative MBC) are intractable to various treatment schemes. Bevacizumab as a novel anti-VEGF drug, its safety for these two high-risk breast cancers remains controversial. Therefore, we conducted this meta-analysis to assess the safety of Bevacizumab for TNBC and HER-2 negative MBC. Methods: We searched Medline, Embase, Web of science and Cochrane databases updated to 1 Oct 2022 for relevant randomized controlled trials (RCTs). In all, 18 RCTs articles with 12,664 female patients were included. We used any grade Adverse Events (AEs) and grade ≥3 AEs to assess the AEs of Bevacizumab. Results: Our study demonstrated that the application of Bevacizumab was associated with increased incidence of grade ≥3 AEs (RR = 1.37, 95% CI 1.30–1.45, Rate: 52.59% vs. 41.32%). Any grade AEs (RR = 1.06, 95% CI 1.04–1.08, Rate: 64.55% vs. 70.59%) did not show a significant statistical difference in both overall results and among the subgroups. In subgroup analysis, HER-2 negative MBC (RR = 1.57, 95% CI 1.41–1.75, Rate: 39.49% vs. 25.6%), dosage over 15 mg/3w (RR = 1.44, 95% CI 1.07–1.92, Rate: 28.67% vs. 19.93%) and endocrine therapy (ET) (RR = 2.32, 95% CI 1.73–3.12, Rate: 31.17% vs. 13.42%) were associated with higher risk of grade ≥3 AEs. Of all graded ≥3 AEs, proteinuria (RR = 9.22, 95%CI 4.49–18.93, Rate: 4.22% vs. 0.38%), mucosal inflammation (RR = 8.12, 95%CI 2.46–26.77, Rate: 3.49% vs. 0.43%), palmar-plantar erythrodysesthesia syndrome (RR = 6.95, 95%CI 2.47–19.57, Rate: 6.01% vs. 0.87%), increased Alanine aminotransferase (ALT) (RR = 6.95, 95%CI 1.59–30.38, Rate: 3.13% vs. 0.24%) and hypertension (RR = 4.94, 95%CI 3.84–6.35, Rate: 9.44% vs. 2.02%) had the top five risk ratios. Conclusion: The addition of Bevacizumab for TNBC and HER-2 negative MBC patients showed an increased incidence of AEs especially for grade ≥3 AEs. The risk of developing different AEs varies mostly dependent on the type of breast cancer and combined therapy. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/#recordDetails], identifier [CRD42022354743].